Pengaruh Kemandirian Belajar, Gaya Mengajar, Dan Interaksi Sosial Terhadap Keaktifan Belajar Siswa SMP Islam Plus Al-Azhar Kota Mojokerto - Nada, Ihrisa Qurrotun; El-Yunusi, Muhammad Yusron Maulana; Darmawan, Didit (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2024)
This research aims to analyze the influence of learning independence, teaching style, and social interaction on the active learning of students at Islam Plus Al-Azhar Middle School, Mojokerto City. Quantitative type of research. Data collection using questionnaires, data analysis using t test, f test and regression. Based on research examining the influence of learning independence, teaching style, and social interaction on students' active learning at Islamic Plus Al-Azhar Middle School, Mojokerto City, it was concluded that these three factors had a significant effect on student involvement and participation in learning. their learning process. Independent learning fosters self-motivation and accountability, encouraging students to play an active role in their education. An effective teaching style, which adapts to student needs and preferences, creates an engaging and supportive learning environment that increases student participation. In addition, positive social interactions between students and between students and teachers encourage a collaborative and dynamic classroom atmosphere, thus further increasing learning activity. Therefore, fostering a balanced combination of these elements is critical to maximizing student engagement and academic success.